Secular state and expression of faith from the public: The limit between religion and impartiality by high ranking officials - Vargas Gutiérrez, Jorge Humberto; Yepes Gómez, Fernando (DIXI, 2023)
Introduction: The principle of constitutional secularism, as a legal guarantee, entails religious freedom at its core given its recognition as a fundamental right. It is institutionally and politically correct in terms of respect and tolerance. However, senior State officials warn how, in the midst of the legitimate exercise of the administrative function, speeches with a marked Catholic religious context are publicly resorted to. As an analytical and supportive exercise, two specific facts are used that show the unjustified violation of said principle, in terms of protection against the president and vice president of Colombia in the four-year period 2018-2022. Without a doubt, it is pertinent to highlight that, especially the Constitutional Court through Ruling T-124 of 2021, set a precedent and ultimately ensured the validity of a secular State where in some way the inveterate connection between the State and the Catholic Church does not prevail. The article opens the imperative debate from and towards the public and the citizen, religious or not, in search of minimum respect for the principle of secularism, in this case by high-ranking officials.Purpose: The principle of secularism, constitutionally and legally enshrined, seems not to have sufficient popular roots to respect openly opposed religious and minority tendencies. It is necessary to identify its true fundamental core as a principle, which allows for more rigorous rules, especially in the face of religious manifestations by high-ranking officials.Description: The history of Colombia has been marked by a strong State-Catholic Church bond. With the advent of the constitutional State and the course of respect and safeguarding of human rights as a limit to power, this union was diluted. The current principle of secularism aims to respect any religious manifestation or belief. However, with the approval of some judicial decisions in the closing phase, the adherence to certain positions and decisions of high public leaders is apparently safeguarded, as well as their inclination towards religiosity, even when it is believed that it has already been overcome.Perspectives: The consecration and legal development, although punctual, of the principle of secularism or religious impartiality call into question the separation of the State and religion. Although respect for all religion is constitutionally recognized, its rules still guarantee to protect the believer and not the agnostics or atheists under the same conditions.
Keywords: Atheist; neutrality; official; popular roots; religious impartiality; secularism